Clinical evaluation of urine laminin‐γ2 monomer as a potent biomarker for non‐muscle invasive bladder cancer. (4th August 2022) - Karashima, Takashi; Umemoto, Susumu; Kishida, Takeshi; Osaka, Kimito; Nakagawa, Masatoshi; Yoshida, Eisaku; Yoshimura, Toru; Sakaguchi, Masahiko; Nishimoto, Hiroyuki; Tai, Mami; Inoue, Keiji; Seiki, Motoharu; et al.
Abstract: Background: To evaluate whether urine laminin‐γ2 monomer (Ln‐γ2m) offers a useful biomarker for patients with non‐muscle‐invasive bladder cancer (NMIBC). Methods: Participants comprised 297 patients, including 111 patients with NMIBC, 136 patients with benign genitourinary disease (BD) and 50 healthy donors (HD). Urine Ln‐γ2m was prospectively measured and accuracy was analyzed. Receiver operating characteristic (ROC) curves were determined and area under the ROC curve (AUC) was calculated for urine Ln‐γ2m, and compared to those of traditional urine tumor markers such as nuclear matrix protein 22 (NMP22), bladder tumor antigen (BTA) and cytology. The net benefits of combining urine markers were analyzed by decision curve analysis. Results: Mean urine Ln‐γ2m was significantly higher in NMIBC than in BD or HD. The AUC for urine Ln‐γ2m was significantly higher than those for urine NMP22, BTA or cytology when comparing NMIBC with HD. In patients with low‐grade NMIBC, the AUC for urine Ln‐γ2m was higher than the AUCs for NMP22, BTA or cytology. A net benefit of combined examination using urine Ln‐γ2m/uCRN with NMP22 was demonstrated. Conclusion: These results suggest urine Ln‐γ2m as a potentially useful biomarker for NMIBC, particularly in cases of low‐grade cancer. Abstract : To evaluate whether measurement of urine laminin‐γ2 monomer (Ln‐γ2m) offers a useful biomarker for patients with non‐muscle invasive bladder cancer (NMIBC). The measurement of urine Ln‐γ2m offers a potentially useful biomarker for NMIBC, particularly in cases of low‐grade cancer.